Antibacterial Activity of Essential Oils and Trametes versicolor Extract against Clavibacter michiganensis subsp. michiganensis and Ralstonia solanacearum for Seed Treatment and Development of a Rapid In Vivo Assay - Laura Orzali; Maria Teresa Valente; Valeria Scala; Stefania Loreti; Nicoletta Pucci (MDPI AG, 2020)
Clavibacter michiganensis subsp. michiganensis (Smith) Davis et al. (Cmm) and Ralstonia solanacearum Yabuuchi et al. (Smith) (Rs) are important seed-borne bacterial pathogens of tomato (Solanum lycopersicum) listed as A2 pests in the EPPO (European and Mediterranean Plant Protection Organization) region. At present, there are few strategies to control these pathogens, and seed control with eco-compatible approaches is widely encouraged. In this work, the essential oils (EOs) of oregano (Origanum vulgare), garlic (Allium sativum), basil (Ocimum basilicum), cinnamon (Cinnamomum zeylanicum), clove buds (Syzygium aromaticum), thyme (Thymus vulgaris), and Trametes versicolor extract (Tve) were tested in vitro for their antimicrobial activity against Cmm and Rs (broth microdilution method). The tested EOs and the Tve extract caused a significant inhibition of bacterial growth, with very promising MBC (minimum bactericidal concentration) and MIC90 (minimum inhibitory concentration causing a 90% growth inhibition) values. Moreover, an in vivo germination test showed no major reduction in seed germination when the substances were applied as seed treatment. A rapid molecular screening method has been developed, through real-time PCR, for the specific quantification of Cmm in the presence of a vegetable matrix to test in vivo the antimicrobial efficacy of oregano and cinnamon oil on seed treatment without resorting to whole plant essays, which are time- and space-consuming.